A Roadmap for Internalization and Implementation of a Respectful Workplace Policy in a Mining Company: Results of a Modified Delphi Survey Study - Lucy Kartikasari; Aurik Gustomo (Dinasti International Journal of Education Management And Social Science, 2025)
The implementation of a respectful workplace policy plays a crucial role in fostering a safe, inclusive, comfortable, and productive work atmosphere—particularly in the mining industry, which is known for its dynamic and complex operational environment. This research aimed to explore and determine effective strategies for implementing such a policy, with the goal of nurturing a culture rooted in mutual respect and aligned with organizational values and strategic objectives. The study employed a modified Delphi method, conducted over several rounds, with participants representing various organizational levels. Programs that achieved at least 75% consensus in the final round were examined further to establish implementation priorities based on both their effectiveness, impact and operational relevance. Findings highlighted several critical factors affecting the successful implementation of respectful workplace practices, including organizational culture, leadership and management commitment, alignment with corporate strategy, company core values, as well as communication and human resources practices. Strategies linked to these key elements were carried out simultaneously, incorporating initiatives such as embedding a culture of respect, enhancing HR competencies, building supportive infrastructure, launching an independent whistleblower system, and rolling out a comprehensive campaign across all operational units. Leadership emerged as a vital driver, responsible for accelerating progress and reinforcing an inclusive work environment. The respectful workplace policy must be systematically integrated into the company’s broader culture and strategic framework to ensure its long-term success.